Analysis of Vibration Generated by the Rubbing of Flat Surfaces - Fuadi, Zahrul (UI Scholars Hub, 2014)
Among the phenomena that occur as a result of contact between two surfaces is friction sound, in which surface roughness is of great importance. In this study, the parameter of contact stiffness is used to explain the frequency characteristic of vibration generated by the rubbing of flat surfaces under a small load. A 3-disk configuration rubbing method was used, which provides a unique characteristic of the system's frequency response function containing specific information about the rubbing vibrations. It is shown that the peak frequency of the rubbing vibration can be explained by using a two-degrees-of-freedom model incorporating the parameter of contact stiffness. A quantitative relationship between the surface roughness and the peak frequency of the rubbing vibrations was established.